2012
DOI: 10.1016/j.aquaculture.2012.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance, ontogeny of osmoregulation and zootechnical improvement in the larval rearing of the Caledonian Blue Shrimp, Litopenaeus stylirostris (Decapoda, Penaeidae)

Abstract: Highlights► Osmoregulation capacity in L. stylirostris is weak in the early life stage. ► Postlarvae progressively acquired the adult pattern of hyper-hypo-osmoregulation. ► At PL9, the estimated isosmotic salinity was 24.5 ppt (720 mOsm.kg − 1 ). ► A two-fold-growth in 19 days-old postlarvae was obtained in dilute seawater compared to seawater conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
4
16
1
7
Order By: Relevance
“…Higher survival rates and greater progress in the larval development of shrimp are directly related to appropriate maintenance conditions (7,13); nevertheless, some researchers who studied the combined effect of salinity and temperature in L. vannamei concluded that biomass respiration, excretion and growth were the best survival indicators (19)(20)(21). As in this study, other authors have reported that salinity and temperature have an influence on the larval development index of Penaeus merguiensis and on the survival of Litopenaeus stylirostris (5,22).…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Higher survival rates and greater progress in the larval development of shrimp are directly related to appropriate maintenance conditions (7,13); nevertheless, some researchers who studied the combined effect of salinity and temperature in L. vannamei concluded that biomass respiration, excretion and growth were the best survival indicators (19)(20)(21). As in this study, other authors have reported that salinity and temperature have an influence on the larval development index of Penaeus merguiensis and on the survival of Litopenaeus stylirostris (5,22).…”
Section: Discussionsupporting
confidence: 56%
“…Nevertheless, it is known that L. vannamei larval stages (nauplius, zoea, mysis) and PL1 can tolerate salinities between 20 and 45ups (6), due to the fact that it is a euryhaline species under natural conditions (24). Nevertheless, there is evidence to show that penaeidae larvae are less resistant to abrupt salinity and temperature variations (22), mainly due to the fact that its gills and other structures specialized in osmoregulation have not developed completely.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations